Determinación del incremento medio anual (IMA) en una plantación de Gmelina arborea Roxb. (melina) en la finca “Los Guayacanes” ubicada en el cantón La Maná, provincia de Cotopaxi - Navarrete Cevallos, Sebastián Alejandro (2021)
Currently, forest plantations play a fundamental role in the country's economy. Historically, Ecuador has been one of the countries that has provided high percentages of wood to the international market. The objective is to determine the mean annual increase (IMA) in a Gmelina arborea Roxb plantation. of 27 ha; in La Mana canton, Cotopaxi province. In the present research project, a completely random design was applied. It consists of 8 plots in which diameter and height data were taken, the same ones that were tabulated in Excel for the calculations of basal area, total and commercial volume, and the IMA of the dasometric variables of melina. The results show that the melina in this site presents acceptable growths, according to the averages obtained for DAP 18.61 cm; 11.61 m in total height; basal area 0.2923 m2. The mean annual increase of Gmelina arborea at four years of age in DBH was 4.65 cm and in total height 2.91 m while in basal area it was 0.07 m3 and in total volume of 0.61 m3. Regarding the total volume per hectare, it was 48.95 m3 and the total volume was 1321.53 m3. While the commercial volume of the plantation Key words: dasometric, volume, variables, plots